2013
DOI: 10.1016/j.ijsu.2012.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic adrenalectomy, a safe procedure for pheochromocytoma. A retrospective review of clinical series

Abstract: As a surgical treatment of pheochromocytomas, laparoscopic adrenalectomy is an effective and safe approach, in selected cases even for PCCs >6 cm in diameter, although patients with such large tumors may have a higher conversion rate and more intraoperative hypertensive crises. Preoperative selective adrenergic blockade does not prevent intraoperative hypertensive crises, but by facilitating the pharmacological management of the perioperative haemodynamic instability, may avoid the onset of major adverse cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
83
1
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(92 citation statements)
references
References 28 publications
4
83
1
4
Order By: Relevance
“…This technique was described for the first time by Gagner in 1992 [1] and in the past years several studies have shown the advantages of laparoscopic approach [2] with decrease of the perioperative morbidity, lower complication rates, less operative blood loss, less postoperative pain and shorter hospital stay compared with open adrenalectomy [3]. On the contrary there are several doubts about laparoscopic approach in case of adrenocortical carcinoma [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…This technique was described for the first time by Gagner in 1992 [1] and in the past years several studies have shown the advantages of laparoscopic approach [2] with decrease of the perioperative morbidity, lower complication rates, less operative blood loss, less postoperative pain and shorter hospital stay compared with open adrenalectomy [3]. On the contrary there are several doubts about laparoscopic approach in case of adrenocortical carcinoma [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…haemodynamic disorders due to excessive manipulations [5]. Currently, the minimally invasive adrenalectomy is successfully used in more than 90% of phaeochromocytoma cases, preceded by preoperative pharmacotherapy to inhibit the hormonal activity of the tumor [6][7][8][9].…”
mentioning
confidence: 99%
“…Radical surgical resection is the treatment of choice for giant extra-adrenal pheochromocytomas [2]. Although preoperative selective angioembolization does not prevent intraoperative hypertensive crises, by facilitating the pharmacological management of the perioperative hemodynamic instability, we may avoid the onset of major adverse cardiovascular complications [7]; however, we have not found it to be necessary as adequate preoperative adrenergic blockade, careful intraoperative tumor handling, and early ligation of the feeding vessels as guided by the imaging prevented fluctuations of blood pressure in the intraoperative period. …”
Section: Discussionmentioning
confidence: 99%